Expression and Release of Tumor Cell Tissue Factor Triggers Recurrent Thromboembolism in a Patient with Endometrial Cancer - Beckmann, Lennart; Lennartz, Maximilian; Poch, Annika; Holstein, Katharina; Bokemeyer, Carsten; Langer, Florian (Hämostaseologie, 2023)
Although cancer-associated thrombosis (CAT) is a frequent complication in patients with malignancies, its treatment remains a challenge in daily practice. Here, we report the clinical course of a 51-year-old woman presenting with a highly thrombogenic paraneoplastic coagulopathy. Despite therapeutic anticoagulation with various agents, including rivaroxaban, fondaparinux, and low-molecular-weight heparin, the patient suffered from recurrent venous and arterial thromboembolism. Locally advanced endometrial cancer was identified. Tumor cells showed strong expression of tissue factor (TF), and significant concentrations of TF-bearing microvesicles were detected in patient plasma. Coagulopathy was controlled only by continuous intravenous anticoagulation with the direct thrombin inhibitor, argatroban. Multimodal antineoplastic treatment, including neoadjuvant chemotherapy followed by surgery and postoperative radiotherapy, resulted in clinical cancer remission, which was paralleled by normalization of tumor markers, CA125 and CA19–9, D-dimer levels, and TF-bearing microvesicles. In summary, continuous anticoagulation with argatroban and multimodal anticancer treatment may be necessary to control TF-driven coagulation activation with recurrent CAT in endometrial cancer.
Keywords: cancer-associated thrombosis; paraneoplastic coagulopathy; tissue factor; endometrial cancer; microvesicle